Analisis de la percepcion sobre la etica profecional del revisor fiscal estudiantes de noveno semestre de contaduria publica de la universidad Antonio Nariño sede Santa Marta (2022)
The ethics of the statutory auditor plays a role in the assertive development of the activities of the professional accountant. Therefore, the objective of the research was to analyze the perception of the ninth-semester public accounting students at the Antonio Nariño University, Santa Marta, about the professional ethics of the statutory auditor. The methodology was of a quantitative approach, non-experimental design, and descriptive type, applying a survey to inquire about the knowledge in ethics of the statutory auditor of public accounting students who were in the ninth semester at the Antonio Nariño University, Santa Marta, being the sample of 15 students. The results reflect that the students have little knowledge regarding the ethics of the statutory auditor, especially in what corresponds to the foundations and normative guidelines that regulate their activities. Likewise, a series of recommendations were presented for the inclusion of the ethics of the public accountant in a transversal way in other subjects in which values and principles in accordance with the exercise of the accountant can be promoted, specifying later in the statutory auditor.